Differential associations of emotional and physical domains of the MacNew Heart with changes in 6-minute walking test. (3rd October 2022) - Jellestad, L; Meier, V G; Bierbauer, W; Bermudez, T; Auschra, B; Gunther, M P; Scholz, U; Von Kanel, R; Hermann, M; Euler, S
Abstract: Aims: Cardiac rehabilitation (CR), a key component of secondary prevention in cardiac patients, contributes fundamentally to improved cardiovascular health outcomes. Health-related quality of life (HRQOL) represents a widely employed outcome measure in CR, yet, its predictive properties on exercise capacity change during CR are poorly understood. Aim of this study was to examine the association between baseline HRQOL and its subdomains on improvement of exercise capacity during CR. Methods: Study participants were 13, 717 inpatients of six Swiss CR clinics from 2012 to 2018. We measured HRQOL at admission to CR with the MacNew Heart (MNH) questionnaire and exercise capacity at admission and discharge using the six-minutes walking test (6MWT). Following factorial analyses, we performed univariate and multivariate analyses to test the predictive properties of baseline global HRQOL and its domains for improvement in exercise capacity, adjusting for demographic and clinical characteristics. Results: Mean improvement in 6MWT was 114 meters (SD=90), achieved after 17.4 days (SD=5.5). Lower emotional HRQOL (b=7.85, p≤0.001, 95% CI [−5.67, 10.03]) and higher physical HRQOL (b=−5.23, p<0.001, 95% CI [−6.56, −3.90]) were associated with less improvement in the 6MWT. Global MNH and social HRQOL showed no association with exercise capacity improvement. Conclusion: Patients entering CR with low emotional and high physical HRQOL are at risk for a lower gain in exercise capacity during CR. Global MNH alone does not provide a reliable assessment of HRQOL; thus a focus on specific domains of HRQOL is needed. Funding Acknowledgement: Type of funding sources: None.